STUDI ETNOGRAFI KULINER LEGENDARIS DI KAWASAN GLODOK - Dea Fernanda; Yudhiet Fajar Dewantara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study discusses the existence of legendary cuisine in the Glodok Chinatown area of Jakarta as a cultural heritage that reflects the social, cultural, and historical values of the Chinese community. The issue raised is the decline in legendary cuisine due to a lack of regeneration of business operators. The objective of this study is to explore and document the gastronomic value of Glodok's legendary cuisine through an ethnographic approach. The research method employed is a descriptive qualitative study with an ethnographic approach. The population in this study is all legendary culinary business operators in Glodok, while the sample focuses on three stalls that have existed for decades, namely Kopi Es Tak Kie (since 1927), Kari Lam (since 1973), and Laksa Lao Hoe (since 1980). Data collection techniques were conducted through direct observation, in-depth interviews, and documentation. Data analysis techniques were carried out through the stages of data reduction, data presentation, and descriptive qualitative conclusion drawing. This study utilized nine components of gastronomy according to Turgarini, such as history, raw materials, presentation, tasting, ethics and etiquette, and dining experience. The results of the study show that these three cuisines still maintain their original flavors, ingredients, and strong traditional values, and have become unique gastronomic tourist attractions. However, the sustainability of these cuisines depends on the willingness of the younger generation to preserve this cultural heritage. This study contributes to the preservation of culinary culture as part of the city's identity and efforts to develop sustainable tourism.